1997
DOI: 10.1148/radiology.202.2.9015061
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant hepatic failure: observation with serial CT.

Abstract: Liver volumes at the initial and last CT examinations and an increase in or late occurrence of ascites are useful prognostic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…In that respect, the application of preoperative imaging techniques might be of assistance as suggested in 2 studies. 3,14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that respect, the application of preoperative imaging techniques might be of assistance as suggested in 2 studies. 3,14 …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] A multicenter European study, 1 including cases from this institution, showed that 19 (63%) of 30 patients with ALF treated by ALT were alive after a mean follow-up of 18 months, with 13 (68%) of these survivors having regained normal native liver function that allowed permanent withdrawal of immunosuppression. Following ALT, immunosuppression can be withdrawn in a significant proportion of patients.…”
mentioning
confidence: 99%
“…Other prognostic criteria have been proposed including severity of SIRS, 117,118 Alpha fetoprotein (AFP) levels, 172 ratios of factor VIII and factor V, 173 liver histology, 174 CT scanning of the liver, 174,175 cytokine levels, 176 serum phosphate levels, 163,177 and adrenal insufficiency. 178 Evaluations of these criteria have had varied results; while some appear promising, more research is needed to determine their reliability.…”
Section: Prognosismentioning
confidence: 99%
“…Multiple prognostic models have been proposed to help determine the likelihood of spontaneous survival (Table 2) (Antoniades et al, 2007;Bailey et al, 2003;Bernuau et al, 1986b;Bernuau, 1993;Craig et al, 2010;Harrison et al, 1990;Itai et al, 1997;O'Grady et al, 1989;Pereira et al, 1992;Rolando et al, 2000;Schiodt et al, 2005;Van Thiel, 1993). However, many of these models are methodologically flawed and subject to bias.…”
Section: Prognostic Modelsmentioning
confidence: 99%